2006
DOI: 10.1182/blood-2006-04-016451
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1: a key effector of regulation mediated by CD4+CD25+ T cells

Abstract: The naturally occurring population of dedicated regulatory T cells that coexpress CD4 and CD25 is known to play a key role in the maintenance of peripheral T-cell tolerance; however, their mechanism of action has remained obscure. Here we report that a member of the family of ␤-galactoside-binding proteins, galectin-1, is overexpressed in regulatory T cells, and that expression is increased after activation. Most importantly, blockade of galectin-1 binding significantly reduced the inhibitory effects of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
355
1
19

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(386 citation statements)
references
References 37 publications
11
355
1
19
Order By: Relevance
“…In fact, T reg cells have been reported to exhibit increased ␣2,6 sialylation (compared with effector T cells) (31); this selective sialylation might interfere with Gal1 binding and cell death (32). This hypothesis is further supported by recent studies demonstrating that T reg cells overexpress Gal1 and remain resistant to Gal1-mediated apoptosis (33).…”
Section: Discussionsupporting
confidence: 68%
“…In fact, T reg cells have been reported to exhibit increased ␣2,6 sialylation (compared with effector T cells) (31); this selective sialylation might interfere with Gal1 binding and cell death (32). This hypothesis is further supported by recent studies demonstrating that T reg cells overexpress Gal1 and remain resistant to Gal1-mediated apoptosis (33).…”
Section: Discussionsupporting
confidence: 68%
“…We found that treatment with recombinant galectin-1 in the efferent phase of autoimmune ocular inflammation results in increased IL-10 and TGF-β production and expansion of regulatory T cells in vivo [43]. Interestingly, recent studies demonstrated that galectin-1 and -10 are overexpressed in regulatory T cells, and are critical for the suppressive activity of these cells [49,50]. Further studies are needed to establish a role of galectin-carbohydrate lattices at synapse formation between regulatory and effector T cells.…”
Section: Galectin-glycoprotein Lattices In T Cell Functionsmentioning
confidence: 82%
“…Interestingly, CD4 ϩ CD25 ϩ regulatory T cells have been shown to mediate their suppressive activity through gal1 (40).…”
Section: Discussionmentioning
confidence: 99%